Validation of an enzyme-linked immunosorbent assay developed for measuring cortisol concentration in human saliva and serum for its applicability to analyze cortisol in pig saliva - Thomsson, Ola (BioMed Central, 2014)
BACKGROUND: The purpose of this study was to validate a commercially available enzyme-linked immunosorbent assay (ELISA) developed for measuring free cortisol in human saliva and total cortisol concentration in diluted human serum, for its applicability in measuring cortisol concentration in pig saliva. Collection of saliva is less stressful than e.g. blood sampling, and is a non-invasive method. FINDINGS: Saliva was collected by allowing sows to chew on cotton swabs held by forceps. Thereafter, the swabs were centrifuged to retrieve the saliva. The ELISA was performed according to instructions provided by the manufacturer. To validate the ELISA, determination of the intra-assay coefficient of variation (CV), inter-assay CV, recovery, linearity and parallelism was performed. The intra-assay CV was below 10% and inter-assay CV below 15% for samples of high, medium and low cortisol concentrations. The mean recovery was 117% and the linearity and parallelism showed an r(2)-value of 0.994 and 0.993, respectively. For biological assessment of induced social stress, two saliva samples were collected in the morning from 6 primiparous and 21 multiparous sows. One sample was collected when the sows were individually housed in a farrowing pen and a second sample was collected when the sows were group housed. The primiparous sows had a significant higher cortisol concentration compared to the multiparous sows when group housed. CONCLUSION: The results obtained in this validation study indicate that the ELISA is suitable for measuring cortisol concentration in porcine saliva.